NRL-GMO: GMOSeek research project (2009 - 2011) for GMO detection361 - Sylvia Broeders; E. Barbau-Piednoir; G.E. Mbongolo-Mbella; N. Papazova; Pouppez,A.; Nancy Roosens; Isabel Taverniers; M. De Loose; Frédéric Debode; Berben,G.; Eric Janssen (LabInfo, 2012)
no abstract
Keywords: 2009; abstract; detection; GMO; GMO detection; GMOseek; Project; Research